Effects of ethanol enrichment on in-cylinder thermochemical fuel reforming (TFR) spark ignition natural gas engine. (1st June 2017) - He, Zhuoyao; Zhu, Lei; Xu, Zhen; Kaario, Ossi; Li, Ang; Huang, Zhen
Highlights: In-cylinder TFR produces substantial H2 and CO. Ethanol helps to better in-cylinder TFR quality. Ethanol smoothens in-cylinder TFR engine operation. Abstract: In this study, the concept of in-cylinder thermochemical fuel reforming (TFR), which involves running one cylinder rich of stoichiometric and routing its entire exhaust back into the intake manifold, were examined on a four-cylinder spark ignition natural gas (NG) engine. Extra natural gas fuel (NG enrichment) was port injected into cylinder #4 (TFR cylinder) to realize its rich running. Results indicated that the combustion of cylinder #2 (typical of cylinder #1, 2 and 3) was significantly improved with substantial H2 and CO fraction in the reformed gas when equivalence ratio of TFR cylinder ( Φ TFR ) was about 1.25. However, not only the stability of TFR cylinder was worsened, but also the discrepancy of IMEP between cylinder #2 and TFR cylinder remarkably increased with the increase of Φ TFR . To improve engine performances, a trial of enriching TFR cylinder using ethanol instead of NG was performed. Results manifested that ethanol enrichment improved H2 and CO concentration in reformed gas and led to a more stable engine operation. Besides, ethanol enrichment also lowered the discrepancy of IMEP between cylinder #2 and TFR cylinder, indicating a better engine uniformity. However, ethanol enrichment did not severely affect engine HC and CO emissions while remarkably lowered NOx emission compared with NG enrichment.